PENGARUH KEBIJAKAN UTANG, LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Chasana, Nurul; Tulhusnah, Lusiana; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
The LQ45 Index is one of the stock price indices. Selecting stock values ​​with a high level of liquidity can be the right choice for investors to reduce the risk of future losses. The shares of companies listed in the LQ45 Index are a collection of 45 companies with liquidity selected with various selection criteria. The level of liquidity in the LQ45 Index has high stocks and a large market capitalization. This study aims to determine the effect of Debt Policy, Liquidity, and Profitability on Company Value with Stock Price in LQ45 companies as an intervening variable. This study uses a quantitative research method. The population in this study consisted of companies listed in the LQ45 Index, with a sample of 12 companies. The sampling technique used in this study is purposive sampling. This study's data analysis and hypothesis testing used the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results of hypothesis testing regarding the direct impact using Smart PLS 3.0 show that debt policy has a negative but insignificant effect on stock prices, liquidity has a negative but insignificant effect on stock prices, profitability has a significant negative effect on stock prices, debt policy has a significant negative effect on company value, liquidity has a significant negative effect on company value, profitability has a negative but insignificant effect on company value, stock prices have a negative but insignificant effect on company value. The indirect effect hypothesis test results show that the debt policy variable has a positive but insignificant effect on company value through stock prices, liquidity has a positive but insignificant effect on company value through stock prices, and profitability has a positive but insignificant effect on company value through stock prices.